Treatment of Dyslipidemia with Statins and Physical Exercises: Recent Findings of Skeletal Muscle Responses - Bonfim, Mariana Rotta (2015)
Statin treatment in association with physical exercise practice can substantially reduce cardiovascular mortality risk of dyslipidemic individuals, but this practice is associated with myopathic event exacerbation. This study aimed to present the most recent results of specific literature about the effects of statins and its association with physical exercise on skeletal musculature. Thus, a literature review was performed using PubMed and SciELO databases, through the combination of the keywords “statin” AND “exercise” AND “muscle”, restricting the selection to original studies published between January 1990 and November 2013. Sixteen studies evaluating the effects of statins in association with acute or chronic exercises on skeletal muscle were analyzed. Study results indicate that athletes using statins can experience deleterious effects on skeletal muscle, as the exacerbation of skeletal muscle injuries are more frequent with intense training or acute eccentric and strenuous exercises. Moderate physical training, in turn, when associated to statins does not increase creatine kinase levels or pain reports, but improves muscle and metabolic functions as a consequence of training. Therefore, it is suggested that dyslipidemic patients undergoing statin treatment should be exposed to moderate aerobic training in combination to resistance exercises three times a week, and the provision of physical training prior to drug administration is desirable, whenever possible.